1964
DOI: 10.2136/sssaj1964.03615995002800040020x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Organic Matter and Clay to Soil Cation‐Exchange Capacity as Affected by the pH of the Saturating Solution

Abstract: The effect of pH of the buffered saturating solution on the cation‐exchange capacity (CEC) of 60 Wisconsin soils was determined within the pH range 2.5 to 8.0. The relative contributions of clay and organic matter to total CEC were measured using multiple regression analyses; the independent variables were clay and organic matter contents and the dependent variables, CEC at pH 2.5, 3.5, 5.0, 6.0, 7.0, and 8.0. The average CEC of the organic matter at each pH value was 36, 73, 127, 131, 163, and 213 me. per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
105
0
5

Year Published

1971
1971
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(128 citation statements)
references
References 0 publications
11
105
0
5
Order By: Relevance
“…For example, organic matter content is sometimes estimated from the color value, and "free iron" from the hue and chroma. Equations have been derived to express the cation exchange capacity of certain soils as a function of clay and organic mattel (4). The total iron content of a soil cannot be predicted from color alone (L0), but soil color has been expressed as a function of iron and organic matter contents' pH and type of clay mineral (7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, organic matter content is sometimes estimated from the color value, and "free iron" from the hue and chroma. Equations have been derived to express the cation exchange capacity of certain soils as a function of clay and organic mattel (4). The total iron content of a soil cannot be predicted from color alone (L0), but soil color has been expressed as a function of iron and organic matter contents' pH and type of clay mineral (7).…”
Section: Introductionmentioning
confidence: 99%
“…Cation exchange reactions are vital to such key processes as nutrient leaching, fertilizer-soil interactions, nutrient supply to plants, and pH-buffering (Binkley and Richter 1987;Bouman et al 1995). Soil CEC is a complex characteristic because the measured value depends on several factors, the most important of which are texture, clay mineralogy, organic matter content, pH, and electrolyte concentration of the soil solution (Helling et al 1964;St. Arnaud and Sephton 1972;Rhoades 1982;Curtin et al 1984).…”
mentioning
confidence: 99%
“…Although several workers have succeeded in predicting CEC at a specific pH (Helling et al 1964;St. Arnaud and Sephton 1972), a function that accounts for the pH-dependence of CEC is lacking.…”
mentioning
confidence: 99%
“…He stated that a divalent displacing cation gives higher values than a monovalent cation and even cations of the same valency give different results. HELLING et al ( 9) showed that the CEC value of soil organic matter is highly pH-dependent and increases faster than that of clay between pH 2.5 and 8.0.…”
mentioning
confidence: 99%